Meningkatkan Hasil Belajar Siswa Kelas XII Pada Mata Pelajaran Kewirausahaan Melalui Model Pembelajaran Kooperatif Tipe Group Investigation Di SMK Karya Mandiri - Riyanti, Amsiyah Dwi; Aryani , Rita; Putri, Eka (Jurnal Ekonomika Dan Bisnis (JEBS), 2024)
AMSIYAH DWI RIYANTI, Improving the learning outcomes of grade XII students in entrepreneurship subjects through cooperative learning models of group investigation type at SMK Karya Mandiri, Economic Education Study Program, Faculty of Education, Panca Sakti University Bekasi, 2024. At SMK Karya Mandiri, the learning system that has been implemented so far has not maximized student active involvement, resulting in suboptimal classroom learning experiences. Many students exhibit passive attitudes, which negatively impact their learning outcomes. To address this issue, the Group Investigation learning model has been applied through classroom action research. This model is designed to enhance student participation and learning outcomes in the Entrepreneurship subject. This study aims to evaluate the effectiveness of applying the Group Investigation learning model in improving the learning outcomes of 12th-grade students. In this study, the Group Investigation method was implemented in two cycles, each consisting of four important stages: planning, action, observation, and reflection. Each cycle begins with planning, which includes developing group worksheets used in the learning action. Students work in groups to complete tasks and present their results to the class, while observation and reflection processes are conducted to assess the model's effectiveness. The research results indicate a significant improvement in student learning outcomes after the implementation of this model. In the first cycle, the average class score was 63.97 with a classical completeness rate of 55.89%, where 19 students achieved satisfactory results. However, after applying the model in the second cycle, the average class score increased to 70.73, and the classical completeness rate surged to 82.53%, with 28 students successfully reaching the targeted passing level. These findings affirm that the Group Investigation model can effectively enhance student engagement and learning outcomes in the Entrepreneurship subject, and provides a strong foundation for applying similar methods in other learning contexts.